Variable segment roles: modulation of the packing modes, nanocrystal morphologies and optical emissions. Issue 28 (10th July 2018) - Wang, Sha-Sha; Rong, Rong; Jin, Ling-Zhi; Yang, Shan-Shan; Li, Yin-Xiang; Zhang, He; Xiong, Yu-Wei; Sun, Li-Tao; Cao, Hong-Tao; Xie, Ling-Hai; Huang, Wei
Abstract : With variable segment roles, three isomers exhibited different packing modes, nanocrystal morphologies and photoluminescence properties. Abstract : Three isomers were prepared by covalently grafting carbazole (Cz) onto spiro[fluorene-9, 9′-xanthene] (SFX) at different positions. Due to the complicated and variable roles of molecular segments, an evolution of the corresponding molecular packing mode was realized, accompanied by the change of nanocrystal morphology and photoluminescence properties.